2017
DOI: 10.21767/2254-6081.1000134
|View full text |Cite
|
Sign up to set email alerts
|

Pelargonium graveolens (Rose Geranium) - A Novel Therapeutic Agent for Antibacterial, Antioxidant, Antifungal and Diabetics

Abstract: Objectives: Draw upon published research articles for evidence and comprise the collected evidence in an evaluation of the preserving and therapeutic abilities of Pelargonium graveolens. Design:The articles used as research for this research review were discovered by searching public databases with keywords such as "Pelargonium graveolens", "P. graveolens", "pelargoniums", "rose-scented geranium", and "geraniums." Then the articles were reviewed, summarized, and organized based on findings.Results: Many articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 17 publications
(55 reference statements)
1
10
0
1
Order By: Relevance
“…EOs from O. basilicum and P. graveolens showed moderate anti-bacterial activity corroborating other studies, which found higher effectiveness against Gram positive than Gram negative bacteria [ 25 ]. However, the antimicrobial property of basil EO was reported in other studies, in which a good activity against E. coli related to a significant amount of linalool was evidenced [ 26 ].…”
Section: Discussionsupporting
confidence: 87%
“…EOs from O. basilicum and P. graveolens showed moderate anti-bacterial activity corroborating other studies, which found higher effectiveness against Gram positive than Gram negative bacteria [ 25 ]. However, the antimicrobial property of basil EO was reported in other studies, in which a good activity against E. coli related to a significant amount of linalool was evidenced [ 26 ].…”
Section: Discussionsupporting
confidence: 87%
“…Anti- E. coli activity was exhibited by EOs from Ocimum basilicum and Pelargonium graveolens [ 8 , 17 , 18 ]. The basil EO activity, of different degree in relation to the tested strain, has been related to its significant amount of linalool [ 18 ], as well as the high amounts of oxygenated monoterpenes in geranium EO seems to determine its antimicrobial property [ 8 ].…”
Section: Bacterial Infectionsmentioning
confidence: 99%
“…Originaire d'Afrique du Sud, le Géranium rosat est cultivé dans de nombreuses régions méditerranéennes et subtropicales, et sa localisation détermine fortement sa composition biochimique. La bio-activité de cette plante a été rapportée dans plusieurs travaux (Hamidpour et al, 2017 ;Radan, 2017 ;Labarde, 2017 ;.…”
Section: Introductionunclassified